A new Arab social contract?: Institutional perspectives for economic reform in Arab countries - Benner, Maximilian (Springer, 2020)
Foreword -- List of abbreviations -- Chapter 1. Middle Eastern and North African economies after the “Arab spring” -- Chapter 2. Economic challenges in Arab economies -- Chapter 3. Socio-economic regulation in core Arab economies: Institutional contexts for economic reform -- Chapter 4. Case studies -- Chapter 5. Towards integrated strategies to promote private-sector growth